Healing the Separation in High-Conflict Post-divorce Co-parenting - Stolnicu, Alexandra; De Mol, Jan; Hendrick, Stephan; Gaugue, Justine (Frontiers in Psychology, 2022)
Objective: Our research aim is to enrich the conceptualization of high conflict post-divorce co-parenting by understanding the dynamic process involved. Background: The studied phenomena was explored by linking previous scientific knowledge to practice. Method: We cross-referenced the previous study results (Stolnicu & Hendrick, 2017; Stolnicu, 2020) with the experiences reported by eight professionals and tried to answer the following research question: How professionals’ experience and previous scientific knowledge (Stolnicu & Hendrick, 2017; Stolnicu, 2020) contribute to a better understanding of HC post-divorce co-parenting? Individual face to face interviews were conducted and analyzed regarding the qualitative theoretical reasoning of thematic analysis (Braun & Clarke, 2006). Results: Analysis allowed us to highlight how four main axis are related to HC post-divorce co-parenting: (1) Parents for life, (2) Acting in the child’s best interests, (3) Managing disagreements and (4) Healing the separation. Conclusion: Our findings capture high conflict post-divorce co-parenting as a multidimensional dynamic process. As such, dealing with co-parenting disagreements must be understood as a moment in a process that is influenced by, and influences, other dimensions. Implications: Interventions must consider the four dimensions and their reciprocal interactions. The essential elements underlying parents’ difficulties may reside at a multiplicity of levels: inter-relational, contextual and intrapsychic. Each level contains key potential factors in understanding these families, and in formulating intervention guidelines.